Comparable Exogenous Carbohydrate Oxidation from Lactose or Sucrose during Exercise. Issue 12 (December 2020) - ODELL, OLIVER J.; PODLOGAR, TIM; WALLIS, GARETH A.
ABSTRACT: Purpose: Ingesting readily oxidized carbohydrates (CHO) such as sucrose during exercise can improve endurance performance. Whether lactose can be utilized as a fuel source during exercise is unknown. The purpose of this study was to investigate the metabolic response to lactose ingestion during exercise, compared with sucrose or water. Methods: Eleven participants (age, 22 ± 4 yr; V[Combining Dot Above]O2peak, 50.9 ± 4.7 mL·min −1 ·kg −1 ) cycled at 50% W max for 150 min on five occasions. Participants ingested CHO beverages (lactose or sucrose; 48 g·h −1, 0.8 g·min −1 ) or water throughout exercise. Total substrate and exogenous CHO oxidation was estimated using indirect calorimetry and stable isotope techniques (naturally high 13 C-abundance CHO ingestion). Naturally low 13 C-abundance CHO trials were conducted to correct background shifts in breath 13 CO2 production. Venous blood samples were taken to determine plasma glucose, lactate, and nonesterified fatty acid concentrations. Results: Mean exogenous CHO oxidation rates were comparable with lactose (0.56 ± 0.19 g·min −1 ) and sucrose (0.61 ± 0.10 g·min −1 ; P = 0.49) ingestion. Endogenous CHO oxidation contributed less to energy expenditure in lactose (38% ± 14%) versus water (50% ± 11%, P = 0.01) and sucrose (50% ± 7%, P ⩽ 0.05). Fat oxidation was higher in lactose (42% ± 8%) than in sucrose (28% ± 6%; P ⩽ 0.01); CHO conditions were lower than water (50% ± 11%; P ⩽ 0.05). Plasma glucose was higher in lactose and sucrose than in water ( P ⩽ 0.01); plasma lactate was higher in sucrose than in water ( P ⩽ 0.01); plasma nonesterified fatty acids were higher in water than in sucrose ( P ⩽ 0.01). Conclusions: Lactose and sucrose exhibited similar exogenous CHO oxidation rates during exercise at moderate ingestion rates. Compared with sucrose ingestion, lactose resulted in higher fat and lower endogenous CHO oxidation.